Estudo do perfil motivacional para o aprendizado de química - Corrêa, Roberta Guimarães (2009)
This work analyses the factors that could influences the Chemistry learning. The motivation is considered a fundamental construct for the scholar learning. The motivation is related to internal or external causes that lead an individual to accomplish or not an activity. Those internal and external causes are denominated intrinsic and extrinsic motivation, respectively. Intrinsically motivated students engage in the accomplishment of scholar activities and incline to persist in front of difficulties. Opposite behavior is observed in extrinsically motivated students. 389 students were invited to participate to a course about Metals. 74 have done the registration in the course and 20 registered students have done the course. Data were collected by questionnaires to delineate the motivational profile of the students. The questions were focused on the identification of the motivational orientation of the students. During the analysis of the questionnaires were observed that the students who have not done the registration present less positive motivational profile to the scholar activities than those who have done the registration and those who have participated of the course. Therefore, independently of type of the motivation, intrinsic or extrinsic, the students that demonstrated interest to the course are more motivated to the scholar activities. However, during the course, were observed differences between students. Some engaged yourselves actively and others, mainly in the moments that the activities demand more attention, engaged yourselves superficially. This difference can be related to the type of motivation. Students with intrinsic motivation more positive than extrinsic engage yourselves more in the proposed activities than students with predominant extrinsic motivation. This research allowed verifying that the motivation is related to contextual factors and the characteristics students and this fact must be considered to better comprehend the behavior of classroom students. Some leaning strategies support the occurrence of motivational orientations that will generate different levels of interest to the realization of the activities. However, when significant learning are considered, environments that support the occurrence and maintenance of intrinsic motivation are considered more adequate.